Learning styles of architecture and interior design students: a review of the literature - Kaba, Imene; Abdou, Saliha (Technium Social Sciences Journal, 2022)
Although much has been written about the teaching of architecture, little progress has been made to improve pedagogical approaches. However, there is a consensus in the literature on the fact that educational practices in architecture are old approaches rooted in the traditions of fine arts schools, and the fact that the shift from the teaching paradigm to the learning paradigm places the student central in the learning process. This research is a systematic review of recent literature; it aims to examine the literature of the past 20 years on the learning styles of architecture and interior design students, and the effects of learning styles on their performance scores. The findings reveal the importance of knowing the learning styles to help teachers to adapt a good teaching approach appropriate to improve the academic performance of students, link between learning styles of architecture and interior design students and the pedagogical approaches adopted, and the role of the teacher in changing student learning styles.